End User Searching in the Health Sciences, 1st edition - Wood, M. Sandra (Routledge, 2020)
This book, first published in 1986, provides a comprehensive and detailed look at online biomedical database searching by end users. Experts fully assess the numerous implications of end user searching and synthesize a wide variety of views and successful practices. By examining the types of users, institutional settings, products used, and applications, this important volume probes the specific variations among programs and provides a solid overview of end user searching in the health science field. The volume includes informative chapters on determining content and structure of online educational materials, training the end user, the issues in implementing end user search systems, and much more.